Keterlibatan Fesyen dan Nilai Belanja Hedonis sebagai Prediktor Pembelian Impulsif Studi Empiris di Jawa Barat - Permadi, Indra (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
This study analyzes the influence of fashion involvement and hedonic shopping value on impulse buying among fashion consumers in West Java. Using a quantitative approach with causal explanatory design, data were collected through online questionnaires and analyzed using multiple linear regression. The research findings indicate that both fashion involvement and hedonic shopping value have positive and significant effects on impulse buying individually. Simultaneously, both independent variables demonstrate a strong positive and significant influence on impulse buying. The findings suggest that deep interest in fashion combined with shopping experiences that provide emotional satisfaction are the primary drivers of impulsive purchasing behavior. Managerial implications highlight the need for marketing strategies that focus on strengthening consumer involvement and optimizing hedonic shopping experiences.